Explaining the fall in Coronary Heart Disease mortality in the Republic of Ireland between 2000 and 2015 - IMPACT modelling study. (1st July 2020) - Marasigan, Vivien; Perry, Ivan; Bennett, Kathleen; Balanda, Kevin; Capewell, Simon; O' Flaherty, Martin; Kabir, Zubair
Abstract: Background: To investigate the contribution of individual and population factors to Coronary Heart Disease (CHD) mortality rates in Ireland between 2000 and 2015. Methods: The Irish IMPACT CHD model was utilized with CHD Deaths Prevented or Postponed (DPPs) as outcome. Results: CHD mortality rates in Ireland in those aged 25–84 years fell by 56% (63% in women vs. men 53%), with 4060 fewer deaths than expected in 2015. Improvements in CHD risk factors explained 30% of the decline (785 DPPs in men; 425 in women): [population systolic blood pressure (+25% DPPs), mean cholesterol serum levels (+11%) and smoking prevalence (+5%)]. Additional deaths attributable to rises in diabetes prevalence (−6%), BMI (−4%) and physical inactivity (−2%) negatively impacted DPPs. Increased uptake of cardiology treatments explained 60% of the decline (1620 DPPs in men; 825 in women), particularly secondary prevention and heart failure treatments. Some 10% was unexplained. Conclusion: CHD mortality declined in Ireland between 2000 and 2015, with two-thirds attributable to increased uptake in cardiology treatments and only one-third to improvements in population risk factors, partly reflecting adverse trends in obesity, diabetes and physical inactivity. Additional investments in prevention policies and treatments will be necessary to reduce future CHD deaths. Highlights: Coronary Heart Disease (CHD) death rates halved between 2000 and 2015 in Ireland. 4060 fewer CHD deaths were observed in 2015 than expected. CHD risk factor improvements contributed to 30% of the CHD mortality decline. Improved uptakes in cardiology treatments explained 60% of the CHD decline. Population health gains were reversed due to increase in BMI, diabetes and physical inactivity levels.